1985
DOI: 10.1136/thx.40.9.684
|View full text |Cite
|
Sign up to set email alerts
|

Giant oesophageal hamartoma.

Abstract: Benign tumours of the oesophagus are rare, representing less than 1 % of all oesophageal neoplasms.' Most of them are intramural leiomyomas and other benign tumours encountered only infrequently; among these pedunculated intraluminal hamartomas form a particularly rare group. Special difficulties are associated with their diagnosis, but early detection is important because despite their benign histological nature life threatening sequelae may ensue. We present the case history of a patient with a protracted il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, twenty studies with twenty esophageal hamartoma cases (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been reported and eight of these studies described (4,6,8,10,11) were cervical or upper esophagus hamartomas [Halfhide et al (10) and Ginai et al (11) reported the same case], and five cases (5,7,9,13) were in distal or lower esophagus [one (9) was in Chinese, Table 1]. Several other studies (23-32) also reported congenital esophageal stenosis caused by tracheobronchial remnants.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, twenty studies with twenty esophageal hamartoma cases (1,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been reported and eight of these studies described (4,6,8,10,11) were cervical or upper esophagus hamartomas [Halfhide et al (10) and Ginai et al (11) reported the same case], and five cases (5,7,9,13) were in distal or lower esophagus [one (9) was in Chinese, Table 1]. Several other studies (23-32) also reported congenital esophageal stenosis caused by tracheobronchial remnants.…”
Section: Discussionmentioning
confidence: 99%
“…The most common tumour type is leiomyoma, while other benign tumours are rare, such as neurofibromas (schwannoma), granular cell tumours, hemangiomas, lipomas, and other types of polyps like hamartoma (13). Previous reports have described intraluminal polypomatous descriptions of oesophageal hamartoma or lower intramural oesophageal hamartoma (2,3,5,14) or lower intramural oesophageal hamartoma (4). Hamartoma in cervical oesophagus of adults is extremely rare and only five case reports on this entity have been published this far (2,3,5,8,15).…”
Section: A B C a Bmentioning
confidence: 98%
“…Hamartomas were introduced in 1904 by Albrecht (1) as tumour-like malformations with mixing normal tissue components in the organ in which they occur. Hamartomas of the lung and airways are relatively common tumours, but only a few reports describe a hamartoma of the oesophagus in adults (2)(3)(4)(5)(6)(7)(8). Also, hamartomas of the nasotracheal tract have been presented, and most of them in paediatric population (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rarity, there are no epidemiological data regarding the occurrence of this disease in the esophagus. Limited data have been published as case reports, scattered in sometimes obscure or relatively inaccessible journals (Table) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Most lesions have been discovered as a result of the patient's clinical presentation, for example, the presence of obstruction due to intraluminal growth (4,11) or the regurgitation of a pedunculated tumor (9, 13). Other tumors have been vague or asymptomatic and discovered incidentally in late childhood or adulthood (2, 5, 10), as in the case of the current patient.…”
mentioning
confidence: 99%